2011
DOI: 10.1200/jco.2011.29.7_suppl.158
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific membrane antigen antibody drug conjugate (PSMA ADC): A phase I trial in taxane-refractory prostate cancer.

Abstract: 158 Background: The unique expression of PSMA type II transmembrane glycoprotein on prostate cancer cells provides a potentially attractive target for antibody therapy. PSMA ADC, a fully humanized antibody to PSMA linked to the potent antitubulin agent monomethyl auristatin E (MMAE), binds PSMA and is internalized within the prostate cancer cell where cleavage and release of free MMAE occur, causing cell cycle arrest and apoptosis. We report results from an ongoing phase I dose escalation study of PSMA ADC in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Preclinical activity has been demonstrated in another mAb conjugated to monomethylauristatin E (MMAE) that recognizes the external domain of PSMA [ 78 ]. This work has led to a phase I dose-escalation study that has shown to be tolerated at the initial dose levels [ 79 ]. Additional early-stage clinical work has involved utilizing enzymatic activation to release cytotoxic substances in PSMA positive cells [ 80 ].…”
Section: Anti-prostatic-specific Membrane Antigen Antibody-drug Comentioning
confidence: 99%
“…Preclinical activity has been demonstrated in another mAb conjugated to monomethylauristatin E (MMAE) that recognizes the external domain of PSMA [ 78 ]. This work has led to a phase I dose-escalation study that has shown to be tolerated at the initial dose levels [ 79 ]. Additional early-stage clinical work has involved utilizing enzymatic activation to release cytotoxic substances in PSMA positive cells [ 80 ].…”
Section: Anti-prostatic-specific Membrane Antigen Antibody-drug Comentioning
confidence: 99%